Complement factor H targeting antibody GT103 in refractory non-small cell lung cancer: a phase 1b dose escalation trial - Jeffrey M. Clarke; George R. Simon; Hirva Mamdani; Lin Gu; James E. Herndon; Thomas E. Stinchcombe; Neal Ready; Jeffrey Crawford; Guru Sonpavde; Stephen Balevic; Andrew B. Nixon; Michael Campa; et al. (Nature Communications)
Abstract GT103 is a first-in-class, fully human, IgG3 monoclonal antibody targeting complement factor H that kills tumor cells and promotes anti-cancer immunity in preclinical models. We conducted a first-in-human phase 1b study dose escalation trial of GT103 in refractory non-small cell lung cancer to assess the safety of GT103 (NCT04314089). Dose escalation was performed using a “3 + 3” schema with primary objectives of determining safety, tolerability, PK profile and maximum tolerated dose (MTD) of GT103. Secondary objectives included describing objective response rate, progression-free survival and overall survival. Dose escalation cohorts included GT103 given intravenously at 0.3, 1, 3, 10, and 15 mg/kg every 3 weeks, and 10 mg/kg every 2 weeks. Thirty one patients were enrolled across 3 institutions. Two dose-limiting adverse events were reported: grade 3 acute kidney injury (0.3 mg/kg) and grade 2 colitis (1 mg/kg). No dose-limiting toxicities were noted at the highest dose levels and the MTD was not reached. No objective responses were seen. Stable disease occurred in 9 patients (29%) and the median overall survival was 25.7 weeks (95% confidence interval [CI], 19.1–30.6). Pharmacokinetic analysis confirmed an estimated half life of 6.5 days. The recommended phase 2 dose of GT103 was 10 mg/kg every 3 weeks, however further dose optimization is needed given the absence of an MTD. The study achieved its primary objective of demonstrating safety and tolerability of GT103 in refractory NSCLC.